Promotion of Fruits and Vegetables Consumption: Results of a School-Based Intervention in a Sample of 13-15 Years Old Italian Students - Lazzeri, Giacomo; Pilato, Valentina; Pammolli, Andrea; Simi, Rita; Galeone, Daniela; Balocchini, Emanuela; Giacchi, Mariano Vincenzo (International Journal of Child Health and Nutrition, 2013)
Background: The …e vai con la frutta (let’s go with fruit) project was designed to respond to the worrying low consumption of fruits and vegetable in the large portion of population, especially in youth. The main objective was to increase fruit and vegetable consumptions at school level. Methods: In 2010/11, we randomly selected subjects from middle and high schools in five Italian regions. The subjects were randomly divided into two groups: intervention (I) and control (C). A questionnaire on fruits and vegetables consumption was administered, at the baseline as well as at end of the period. The sample size was evaluated on the expected frequency of 0.5 for a binomial random variable, of ± 1.54% with IC of 95%. Results: These results confirmed that adolescent students at baseline survey eat less than the amount of fruits and vegetables consumption recommended by the International guidelines. After the intervention time, we observed an increment in fruits and vegetables consumptions both in middle and high school students. Regarding the impact of the intervention on the factors like knowledge, attitudes and behaviour, there was a positive change in the behaviour only in the intervention group, in coherence with the consumption variations examined. Conclusions: This study is the first time that fruits and vegetables were offered at such a large scale through vending machines at schools in five regions. Several vending companies under this project agreed to revise the list of healthy snacks offered to eliminate those clearly classified as junk foods.